GREEN LIVESTOCK DEVELOPMENT: THE ROLE OF LACTIC BACTERIA FOR IMPROVEMENT AND UTILISASTION OF TOTAL MIXTURE FORAGE - Bachruddin, Zaenal (2013)
The Objective of this study was utilisation of lactic acid bacteria as inoculant for improvement and utilisation of total mixture forages (TMF) as good and complete ration in establishing of green livestock production. Value Km Analysis of Lactobacillus Plantarum. L. Bulgaricus and L. Casei in define medium with glucose limitation was done. The lowest Km of those microbes with glucose utilisation as carbon sources then is used as inoculant for total mixture forages (TMF-SILAGE). Three kind of different molasses (0.2%, 0.6% and 1.0%) were added at TMF-SILAGE with L.Plantarum as inoculant at 14 and 21 days incubation. The result of study showed that Km of those microbes as followL.plantarum0,2 g/100 ml, L.bulgaricus3.6 g/100mland L.Casei71.7 g/100ml. The lowest pH of TMF-SILAGE with L.Plantarum as inoculant was obtained at 1.0% molasses addition 4.8 (14 days incubation) and 4,51 (21 days incubation). While at 21 days incubation the highest lactate content of TMFSILAGEL. Plantarum as inoculant was obtained at 0.6 % molasses addition was 1031 mg/100 g and at 1.0 % molasses addition was 1210 mg/100 g. The Acetate content TMF-SILAGEL.Plantarum as inoculant at 21 days incubation was obtained as follow 4,06 (0.2% molasses addition), 3,83 (0.6% molasses addition) and 3.73 (1.0% molasses addition). The conclusion of this study was the lowest pH and the highest lactate content of TMF-SILAGE with L.Plantarum as inoculant was obtained either 0,6% and 1.0% molasses addition. Key word: lactic acid bacteria, Km and Total Mixture Forage-SILAGE